A Difficulty Chart for Estimation of Treatment Duration of Palatally Impacted Canines (Medico Legal Update, 2020)
Treatment of maxillary impacted canine is a challenging process to dental specialists and orthodontists.The aim of the present study was to assess the duration of orthodontic treatment of palatally impactedcanines, using a difficulty chart as an estimate of the prognosis, and relating it to the treatment time and toother factors that might affect the treatment duration. A cross-sectional study was undertaken using a selfadministered questionnaire to be completed by orthodontists (82 participants). An index was used as a toolto assess the prognosis and treatment duration. The study found that 48.7% of active orthodontic treatmenttime for palatally impacted canines was completed in 1.5 to 2 years. The number of active treatment visitsper patient was between 16 and 22 (62% of treatment visits). In terms of the treatment performed, 81.7%of cases had space created prior to surgical exposure, and 59.8% had open surgical exposure. Failed toattend visits by the patient accounted for 48.4% and 62.2% did not require repeated surgical exposure.Interestingly, 85% of the cases had ‘good’ or ‘average’ prognosis (49% and 36%, respectively). A prognosticchart can provide an estimate for the treatment time to bring a palatally impacted canine into the arch. Thisinformation might be valuable for both orthodontists and their patients, to estimate the time of the plannedtreatment and provide a valid consent form.